PENYULUHAN MANAJEMEN USAHA BAGI PENGURUS DAN ANGGOTA KOPERASI DI DESA LONTAR KECAMATAN TIRTAYASA KABUPATEN SERANG, BANTEN - Aryani, Lina; Desmintari, Desmintari (Nemui Nyimah, 2021)
Community service is carried out at the cooperative in Lontar village, Serang district, Banten province. The purpose of this community service activity is to provide an introduction to business management for cooperative members in Lontar village, Serang district. The introduction of business management is expected to be able to improve the competence of managers and members, especially in carrying out business management functions, from marketing, finance and human resources. The method of this activity is an introduction to the concept of business management and its role in building competitive advantage. Managers and members are given an understanding of the functions of business management, in order to improve the capabilities of the board and members. Community service activities are carried out using the face-to-face method. Activities are carried out by lecturing on the concepts of business management functions and their application in cooperatives.